تقييم الإشراف العملي من وجهة نظر طلاب كلية التمريض - جامعة تشرين (دراسة وصفية) - اصبيرة, ولاء (Latakia University Journal -Medical Sciences Series, 2017)
هدفت الدراسة إلى تقييم الإشراف العملي من وجهة نظر طلاب كلية التمريض في جامعة تشرين. حيث تكونت العينة من 350 طالب/ة , أخذت عشوائياً من طلاب كلية التمريض في السنوات الأكاديمية الأربعة, ممن تواجدوا أثناء فترة تجميع البيانات. طور الباحث أداة تقييم الإشراف العملي اعتماداً على المراجع الحديثة, و تكونت الأداة من ثلاثة محاور: محور إدارة العملية التعليمية, والمحور التعليمي, ومحور الدعم (التحفيز) ورضا الطلاب عن الإشراف العملي.كانت أهم النتائج وجود فارق بسيط بين آراء الطلاب السلبية والايجابية تجاه الإشراف عليهم في التدريب العملي, حيث كان تقييم الطلاب أكثر ايجابية في محور إدارة العملية التدريبية , بينما كان تقييمهم أكثر سلبية في بقية المحاور(المحور التعليمي, ومحور الدعم أو التحفيز, ورضا الطلاب عن الإشراف العملي).The study aimed to assess the clinical supervision from viewpoint of students of Nursing Faculty in Tishreen University. The study sample consisted of 350 students, randomly selected from the students of Nursing Faculty in The four academic years, who were existed during the period of data collection. The researcher developed the tool of assessing clinical supervision depending on up-to date references, and the tool consisted of three axis: axis of training process management, educational axis, and supportive or motivation axis & students' satisfaction with clinical supervision.The main results of the study were there was a few difference between negative and positive viewpoints of students toward supervision on them in clinical training. Whereas, students' assessment was more positive in axis of training process management, while it was more negative in the remaining axis (educational axis, supportive or motivation axis, and students' satisfaction with clinical supervision.